2017
DOI: 10.1111/1462-2920.13696
|View full text |Cite
|
Sign up to set email alerts
|

The alternative sigma factor σB plays a crucial role in adaptive strategies of Clostridium difficile during gut infection

Abstract: Clostridium difficile is a major cause of diarrhoea associated with antibiotherapy. Exposed to stresses in the gut, C. difficile can survive by inducing protection, detoxification and repair systems. In several firmicutes, most of these systems are controlled by the general stress response involving σ . In this work, we studied the role of σ in the physiopathology of C. difficile. We showed that the survival of the sigB mutant during the stationary phase was reduced. Using a transcriptome analysis, we showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

23
174
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(199 citation statements)
references
References 105 publications
23
174
2
Order By: Relevance
“…tryptone‐yeast extract (TY)] used to propagate C. difficile . However, the survival rate of the sigB mutant in TY medium was much more strongly impaired then its isogenic sigB + parent strain (Kint et al ., ), consistent with the function of SigB as a stationary phase sigma factor. Kint et al .…”
supporting
confidence: 79%
See 4 more Smart Citations
“…tryptone‐yeast extract (TY)] used to propagate C. difficile . However, the survival rate of the sigB mutant in TY medium was much more strongly impaired then its isogenic sigB + parent strain (Kint et al ., ), consistent with the function of SigB as a stationary phase sigma factor. Kint et al .…”
supporting
confidence: 79%
“…Importantly, Kint et al . () found that SigB does not affect the expression of the genes for the TcdA and TcdB toxins present in the strain they studied. Hence, SigB influences pathophysiology and gut colonization by C. difficile in ways that are different from those afforded by the TcdA and TcdB virulence factors (Aktories, ; Abt et al ., ; Janoir, ; Martin‐Verstraete et al ., ).…”
mentioning
confidence: 85%
See 3 more Smart Citations